Improving control of the Mpox outbreak: a national cross-sectional study on the knowledge, attitudes, and influencing factors among frontline healthcare professionals in Ethiopia - Getahun Fetensa; Getahun Fetensa; Getahun Fetensa; Bizuneh Wakuma; Bizuneh Wakuma; Merga Besho; Girma Yadesa; Jilcha Gugsa; Derara Girma Tufa; Feyiso Bati; Kitesa Biresa Duftu; Tadesse Tolossa; et al. (Frontiers in Public Health, 2025)
IntroductionMonkeypox (Mpox) has emerged as a global public health concern, with ongoing outbreaks in non-endemic countries affecting various aspects of the healthcare system. This study aimed to determine the knowledge, attitudes, and factors associated with Mpox among healthcare professionals in Ethiopia.MethodsA national cross-sectional study was conducted in Ethiopia from 31 August 2024 to 10 September 2024, involving 749 frontline healthcare professionals. Data were collected via an online survey using Google Forms, with questionnaires distributed through widely used social media platforms such as Email, Telegram, and WhatsApp. Participants were recruited using a snowball sampling technique to ensure diverse representation among frontline health workers.ResultA total of 749 healthcare professionals participated in the study, yielding a response rate of 93.6%. More than half (56.5%) of the participants demonstrated good knowledge about Mpox, while 51.5% showed a positive attitude toward Mpox. Statistically significant factors associated with better knowledge of healthcare professionals toward Mpox included being male [adjusted odds ratio (AOR) = 1.61], being in the 25–30 years age group (AOR = 2.29), and having a history of coronavirus disease 2019 (COVID-19) vaccination (AOR = 1.84). Factors significantly associated with a positive attitude toward Mpox included having good knowledge (AOR = 1.41), being male (AOR = 2.07), holding a diploma (AOR = 1.96), earning a monthly income between 8,018 and 9,057 ETB (AOR = 2.83), and identifying as an Orthodox Christian (AOR = 1.65).ConclusionKnowledge and attitude toward Mpox and its prevention among healthcare professionals in Ethiopia are found to be suboptimal. Significant efforts are needed to control and prevent outbreaks in Ethiopia by enhancing the capability of healthcare professionals. Factors such as a history of COVID-19 vaccination, male sex, and being in the 25–30 age group were significantly associated with knowledge of the disease and its prevention. Moreover, factors such as male sex, a diploma-level education, monthly income, and being an Orthodox religion follower were linked to positive attitudes toward Mpox and its prevention. Further studies are needed to tackle the perceived challenges of controlling the outbreak among potential stakeholders, including healthcare professionals working in rural areas, to support the current findings.